Two-step förster resonance energy transfer amplification for ratiometric detection of pathogenic bacteria in food samples. (15th March 2023) - Li, Zongbing; Xu, Huanwen; Feng, Qiumei; Zhang, Zifeng; Miao, Xiangmin
Highlights: An radiometric fluorescent biosensor was designed for S. aureus detection. Two-step FRET system was achieved based on a dual-recognition proximity binding-induced TSDR. Such radiometric fluorescent biosensor can effectively reduce the interference of experimental conditions. Satisfactory results were obtained while detecting S. aureus compared with other control bacteria. Abstract: We described a two-step förster resonance energy transfer (FRET) system for ratiometric Staphylococcus aureus ( S. aureus ) detection based on a dual-recognition proximity binding-induced toehold strand displacement reactions (TSDR). Ru(bpy)3 2+ and platinum nanoparticles (Pt NPs) labeled DNA (Ru-S3 and Pt NPs-S4) hybridized to enable the occurrence of the primary FRET using Ru(bpy)3 2+ as the energy donor and Pt NPs as the energy acceptor. TSDR happened by integrating vancomycin hydrochloride labeled S1 (Van-S1) and gold nanoclusters labeled S2-aptamer (Au NCs-S2-aptamer) with S. aureus . The single DNA segments of Van-S1 bond to the terminal toehold of Ru-S3, displacing Pt-S4, inducing the secondary FRET using Au NCs as the energy donor and Ru(bpy)3 2+ as the energy acceptor. This two-step FRET system efficiently improved the reaction efficiency of S. aureus with a detection limit of 1.0 CFU/mL. Furthermore, satisfactory results obtained while detecting S. aureus in food samples, indicating a great potential for food analysis.